Terms of trade and growth of resource economies: A tale of two countries - Augustin Kwasi Fosu (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2011)
The current paper demonstrates a dichotomy of the growth response to changes in the barter terms of trade, employing as case studies the two African countries, Botswana and Nigeria.Using distributed-lag analysis, the paper finds that the effect of terms of trade on output is positive and negative for the two countries, respectively. I interpret these results as supportive of the 'resource curse' hypothesis for Nigeria, but not for Botswana.I further argue that the superior institutional quality in Botswana, relative to Nigeria, is likely responsible for the contrasting results. However, Nigeria appears to be making progress on institutional quality, especially in the last decade. Continuing such progress would be necessary if the country was to reverse course.
Keywords: O13; O43; O55; O57; 330; resource economies; terms of trade; growth; Wirtschaftswachstum; Rohstoffressourcen; Terms of Trade; Botsuana; Nigeria